TIPS FOR PREPARING JOURNALS USING A LITERATURE REVIEW APPROACH FOR MASTER OF MANAGEMENT STUDY PROGRAMS MARSHAL SURYADARMA AEROSPACE UNIVERSITY - Khoirul Anam (PT. Arsil Reka Engineering, 2023)
Cooper (1984) argues that research is a systematic process of inquiry aimed at providing information to solve problems. Research must be based on strong theory and come from reliable sources. The right method for finding a good theory is to conduct a literature review or literature study. A literature review has a review, summary, and author's thoughts about several library sources. The source of the results of research conducted by other researchers must be stated, and the procedure for referring to library sources follows established rules. In the literature review writing library, you will explore studies that people have conducted on a particular topic or issue. In reviewing the literature to produce a scientific article, the author explores literature related to the topic and research problem, society and the research area, theories that have been used and produced by people related to the scientific topic, and research methods used in the study.